IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 19 TAHUN 2016 TENTANG PENGELOLAAN BARANG MILIK DAERAH PADA DINAS KESEHATAN KABUPATEN BANJAR - K Kamarullah; Gerilyansyah Basrindu; Mumammad Jamili (STIA Bina Banua Banjarmasin, 2019)
This study aims to: 1) To find out the implementation of the Minister of Home Affairs regulation number 19 of 2016 on the management of local property in the Health Office of Banjar Regency, 2) To know the factors supporting the implementation of the Minister of Home Affairs regulation number 19 of 2016 on the management of local property on the Department Health of Banjar Regency, 3) To know the factors that hamper the implementation of the regulation of the Minister of Home Affairs number 19 of 2016 on the management of regional property at the Banjar District Health Office, 4) To find out alternative solutions that can be done to overcome the obstacles to the implementation of the Minister of Home Affairs regulation number 19 Year 2016 on the management of property owned by the District Health Office Banjar. The result of the research shows that: 1) The management of local property in the scope of Banjar District Health Office has been guided by the Minister of Home Affairs Regulation No. 19 of 2016 on the Management of Regional Property only in the implementation there are stages that are still not in accordance with the regulation, namely : planning stages, 2) Supporting factors for the implementation of the Regulation of the Minister of Home Affairs Number 19 of 2016 on Management of Regional Property at the Health Office of Banjar Regency, namely: a. The existence of a Decree of the Regent of Banjar on the assessment of the management of BMD in the SOPD of Kabupaten Banjar, and, b. The existence of Socialization of Regulation of Minister of Home Affairs Number 19 Year 2016 About Management of Regional Property. 3) Factors inhibiting the implementation of the regulation of the Minister of Home Affairs number 19 of 2016 on the management of regional property at the Health Office of Banjar Regency, namely: 1) The quality of human resources of the management of goods is still relatively low, 2) facilities and infrastructure are still lacking, 3) planning and budgeting within the Banjar District Health Office, 4) Alternative solutions that can be done to overcome the obstacles to the implementation of the Minister of Home Affairs regulation number 19 of 2016 on the management of regional property at the Health Office of Banjar Regency, namely: 1) Increased education, Knowledge of the Assistant to the Management of Goods on Local Ownership Management Regulation, 2) Improvement of Facilities and Infrastructure, 3) The improvement of coordination in planning and budgeting of expenditure. Penelitian ini bertujuan: 1) Untuk mengetahui implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar, 2) Untuk mengetahui faktor pendukung implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar, 3) Untuk mengetahui faktor penghambat implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar, 4) Untuk mengetahui alternatif solusi yang dapat dilakukan guna mengatasi faktor penghambat implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar. Hasil Penelitian menunjukkan bahwa : 1) Pengelolaan barang milik daerah yang ada di lingkup Dinas Kesehatan Kabupaten Banjar sudah berpedoman pada Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 Tentang Pengelolaan Barang Milik Daerah hanya saja dalam pelaksanaannya ada tahapan yang masih tidak sesuai dengan peraturan tersebut, yaitu : tahapan perencanaan, 2) Faktor pendukung implementasi Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 Tentang Pengelolaan Barang Milik Daerah pada Dinas Kesehatan Kabupaten Banjar, yaitu : a. Adanya Surat Keputusan Bupati Banjar tentang penilaian pengelolaan BMD pada SOPD Kabupaten Banjar, dan, b. Adanya Sosialisasi Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 Tentang Pengelolaan Barang Milik Daerah. 3) Faktor penghambat implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar, yaitu : 1) Kualitas SDM pembantu pengurus barang masih tergolong rendah, 2) sarana dan prasarana masih kurang, 3) Minimya koordinasi dalam perencanaan dan penganggaran di internal Dinas Kesehatan Kabupaten Banjar, 4) Alternatif solusi yang dapat dilakukan untuk mengatasi faktor penghambat implementasi peraturan Menteri Dalam Negeri nomor 19 Tahun 2016 tentang pengelolaan barang milik daerah pada Dinas Kesehatan Kabupaten Banjar, yaitu : 1) Peningkatan pendidikan, wawasan dan pengetahuan pembantu pengurus barang terhadap peraturan pengelolaan barang milik daerah, 2) Peningkatan Sarana dan Prasarana, 3) Peningkaan koordinasi dalam perencanaan dan penganggaran belanja.